PENGEMBANGAN MULTIMEDIA INTERAKTIF SISTUR MUATAN MATERI IPA PADA KELAS VI SEKOLAH DASAR - Agustia Bazalina Bazalina; Hetilaniar Hetilaniar Hetilaniar; Sylvia Lara Syaflin (Universitas Hamzanwadi, 2023)
The problem in this research is that students still find it difficult to understand abstract material and lack the use of learning media. So this research is motivated by obtaining interactive learning multimedia so that it can make it easier for students to learn, and make learning more varied. This research aims to produce interactive multimedia SISTUR science material that is valid and practical. The method used in this research is the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The ADDIE model is synonymous with developing a product for use in learning. The research results show that the SISTUR Interactive Multimedia Science Material Content, which was developed in this research, meets the very valid criteria. There are three aspects assessed in this validity, namely the validity of the media, material and language. From these three validations, a validity value of 91.24% was obtained with the criteria